HIGH HEAT-RESISTANCE Sm-Fe-N-BASED MAGNETIC POWDER AND METHOD OF PRODUCING THE SAME

By plating the Al-Ae alloy film layer on Sm-Fe-N magnetic powder, the problem of coercivity reduction when the magnetic powder is heated in an oxidative atmosphere is solved, and higher thermal stability and applicability are achieved.

JP2025048790APending Publication Date: 2025-04-03DOWA HOLDINGS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024159562
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-20
Filing Date
2024-09-13
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

When the existing Sm-Fe-N magnetic powder is heated in an oxidative atmosphere, the problem of coercivity is reduced, making it difficult to meet the high-temperature molding needs.

Method used

By plating an Al-Ae alloy film layer on the surface of Sm-Fe-N magnetic powder particles, the Al-Ae alloy film layer acts as a barrier layer to prevent oxygen from invasion, thereby improving the thermal stability of the magnetic powder.

Benefits of technology

It significantly improves the coercivity reduction ability of Sm-Fe-N magnetic powder when heated in 300°C oxidation atmosphere, and is suitable for high-temperature molding automotive motor applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048790000001_ABST
    Figure 2025048790000001_ABST
Patent Text Reader

Abstract

To improve the heat resistance of an Sm-Fe-N-based magnetic powder in an oxidizing atmosphere.SOLUTION: A high heat-resistance Sm-Fe-N-based magnetic powder consists of an Sm-Fe-N-based magnetic particle having an Al-Ae-based alloy coat layer on a surface, when an alkaline earth metal element is represented as Ae. The powder has an Sm / Fe molar ratio, for example, of 0.09 or greater and 0.25 or smaller and an N / Fe molar ratio, for example, of 0.06 or greater and 0.30 or smaller. In addition, the powder has a cumulative 50% particle size D50 in a volume-based grain-size distribution by a laser diffraction scattering method, for example, of 0.5 μm or greater and 5.0 μm or smaller. As the alkaline earth metal element Ae, one or more of Mg and Ca, for example, can be adopted. The coat layer can be formed, for example, by carrying out co-sputtering of Al and Ae by using a sputtering film-forming device.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a highly heat-resistant Sm-Fe-N magnetic powder that is excellent in resistance to a decrease in coercivity when heated in an air atmosphere, and a method for producing the same. [Background technology]

[0002] Sm 2 Fe 17 A material in which nitrogen is introduced into an intermetallic compound (the typical composition formula is Sm 2 Fe 17 N 3 ) is known to be a ferromagnetic material that exhibits excellent hard magnetic properties. 2 Fe 17 Powder of a substance in which nitrogen is introduced into an Sm-Fe alloy with a stoichiometric composition or a composition close to the stoichiometric composition, and which is a ferromagnetic material, is called "Sm-Fe-N magnetic powder." Sm-Fe-N magnetic powder is useful as a material for bonded magnets.

[0003] Since the production of bonded magnets requires a process of heat-treating magnetic powder together with a resin binder, the Sm-Fe-N magnetic powder used in bonded magnets must be "heat-resistant" so that the deterioration of its magnetic properties (especially its coercive force) due to the heat treatment is minimized.

[0004] Patent Document 1 discloses a Sm-Fe-N magnetic powder that has a core-shell structure with a shell layer containing Sm and Fe in a specific composition and also contains phosphorus (P). This magnetic powder has excellent heat resistance and can be molded at high temperatures using a binder such as polyphenylene sulfide resin, which has high heat resistance (paragraph 0094). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2022-177699 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for Sm-Fe-N bonded magnets using SPS (syndiotactic polystyrene) resin or PPS (polyphenylene sulfide) resin, which have excellent strength and chemical properties, for use in automobile motors. In order to industrially mass-produce bonded magnets using these resins, heating to about 300°C in air is required. As mentioned above, Patent Document 1 describes polyphenylene sulfide resin. However, the heat resistance evaluation performed in Patent Document 1 is based on heating at 300°C for 90 minutes in an argon atmosphere (paragraph 0106). With the technology of forming a shell layer mainly composed of Sm and Fe disclosed in Patent Document 1, it is difficult to sufficiently suppress the decrease in coercivity when heated to about 300°C in air, which is an oxidizing atmosphere.

[0007] In order to advance the practical application of Sm-Fe-N bonded magnets using the above-mentioned SPS resin or PPS resin, it is necessary to improve the heat resistance of Sm-Fe-N magnetic powder in an oxidizing atmosphere. The present invention aims to provide an Sm-Fe-N magnetic powder with improved heat resistance in an oxidizing atmosphere. [Means for solving the problem]

[0008] The inventors have found that by covering the surface of Sm-Fe-N magnetic particles with an alloy film of Al (aluminum) and an alkaline earth metal element, the heat resistance in air of the powder composed of the magnetic particles, that is, the resistance to coercive force reduction when heated in air at about 300°C, can be significantly improved. As a result of the research, it was thought that the above-mentioned alloy film functions as a barrier layer to prevent the intrusion of oxygen. The alloy film can be formed by a vapor phase growth method that does not easily cause thermal damage to the Sm-Fe-N magnetic particles. In addition, the coating layer can be densified by subjecting the Sm-Fe-N magnetic powder after the formation of the Al-alkaline earth metal alloy coating layer to a heat treatment in which the powder is heated to a predetermined temperature in a non-oxidizing atmosphere. This densification treatment can further improve the resistance to coercive force reduction when heated in air at about 300°C. The present invention is based on such findings.

[0009] The above object can be achieved by the following invention. [1] Highly heat-resistant Sm-Fe-N magnetic powder consisting of Sm-Fe-N magnetic particles having an Al-Ae alloy coating layer on their surfaces, where Ae is an alkaline earth metal element. [2] The highly heat-resistant Sm-Fe-N magnetic powder according to the above [1], in which the Sm / Fe molar ratio is 0.09 or more and 0.25 or less, and the N / Fe molar ratio is 0.06 or more and 0.30 or less. [3] Cumulative 50% particle diameter D in volume-based particle size distribution measured by laser diffraction / scattering method 50 The highly heat-resistant Sm-Fe-N magnetic powder according to the above [1] or [2], wherein the particle size is 0.5 μm or more and 5.0 μm or less, and the coating amount index R represented by the following formula (1) is 0.10 μm or more and 2.00 μm or less. Coverage index R=[(Al+Ae) / Fe]×D 50 …(1) Here, the (Al+Ae) / Fe molar ratio in the powder having an Al-Ae alloy coating layer is substituted for [(Al+Ae) / Fe] in formula (1), and D 50 The cumulative 50% particle diameter D 50 The value in μm is assigned. [4] The highly heat-resistant Sm-Fe-N magnetic powder according to the above [3], wherein the coating amount index R is 0.10 μm or more and 1.00 μm or less. [5] The highly heat-resistant Sm-Fe-N magnetic powder according to any one of the above [1] to [4], wherein the alkaline earth metal element Ae is one or more elements selected from Mg and Ca. [6] When subjected to a heating test in which the material was held in air at 300°C for 120 minutes, the coercive force loss rate ΔH, expressed by the following formula (2), c The highly heat-resistant Sm-Fe-N magnetic powder according to any one of the above [1] to [5], wherein the content of the Sm-Fe-N magnetic powder is 60% or less. δH c =100×(H c0 -H c1 ) / H c0 …(2) Here, H c0 is the coercive force (kA / m) of the powder before the heating test, H c1 is the coercive force (kA / m) of the powder after the heating test.

[0010] [7] A method for producing highly heat-resistant Sm-Fe-N magnetic powder, comprising a coating process for forming a coating layer of an Al-Ae alloy on the surfaces of particles constituting the Sm-Fe-N magnetic powder, which is a coating material, by a vapor phase epitaxy process, where Ae is an alkaline earth metal element. [8] A method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to the above item [7], wherein the vapor deposition method is a sputtering method, and in the film-forming step, a coating layer of an Al-Ae alloy is formed on surfaces of particles constituting the Sm-Fe-N magnetic powder by a sputtering method while stirring and flowing the Sm-Fe-N magnetic powder as a film-forming material in a sputtering film-forming apparatus. [9] The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to the above [7] or [8], wherein the Sm-Fe-N magnetic powder, which is a film-forming material, has a composition in which the Sm / Fe molar ratio is 0.09 or more and 0.25 or less, and the N / Fe molar ratio is 0.06 or more and 0.30 or less.

[10] The Sm-Fe-N magnetic powder, which is the material to be coated, has a cumulative 50% particle diameter D 50and in the film-forming step, Al and an alkaline earth metal element Ae are deposited so that a coverage index R expressed by the above formula (1) is 0.10 μm or more and 2.00 μm or less.

[11] The method for producing the highly heat-resistant Sm-Fe-N magnetic powder according to

[10] above, wherein in the film-forming step, Al and an alkaline earth metal element Ae are deposited so that the coating amount index R is 0.10 μm or more and 1.00 μm or less.

[12] The Sm-Fe-N magnetic powder, which is a film-forming material, a heat treatment process for coarsening the crystal grains of the powder particles by heating the powder of Sm-Fe alloy having a Sm / Fe molar ratio of 0.09 to 0.25 formed during the solidification process by the gas atomization method to a temperature of 900°C to 1200°C; a crushing step of crushing the powder of the Sm-Fe alloy, the crystal grains of which have become coarse by the heat treatment step, to thereby reduce the particles of the powder by fracture, including intragranular fracture; a nitriding step of introducing nitrogen into the particles of the Sm-Fe alloy powder refined by the pulverization step by heating and holding the powder at a temperature of 500°C or less in a nitrogen compound or nitrogen-containing non-oxidizing gas atmosphere; The method for producing the highly heat-resistant Sm-Fe-N magnetic powder according to any one of the above items [7] to

[11] , which is obtained by a production method comprising the steps of:

[13] A densification treatment step in which the Sm-Fe-N magnetic powder obtained in the film-forming step is heated in a non-oxidizing atmosphere to a temperature T (°C) that satisfies the following formula (4): The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to any one of the above items [7] to

[12] , further comprising: 450≦T(℃)≦550 …(4)

[14] In the film forming process, the melting start temperature T M forming an Al-Ae based alloy coating layer having a composition in which the temperature is 600°C or less, A densification process in which the Sm-Fe-N magnetic powder obtained in the film-forming process is heated in a non-oxidizing atmosphere to a temperature T (°C) that satisfies the following formula (3); The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to any one of the above items [7] to

[12] , further comprising: T M (℃)-100≦T(℃)≦550 …(3) Effect of the Invention

[0011] According to the present invention, it is possible to significantly improve the resistance of Sm-Fe-N magnetic powder to coercivity loss when heated in air. The present invention can be applied to the manufacture of bonded magnets involving a process of heating up to about 300°C in air, and can contribute to the practical application of Sm-Fe-N bonded magnets that use resins with excellent strength, heat resistance, and chemical properties, such as SPS resin and PPS resin, as the binder component. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram showing a schematic configuration of a gas atomizing device used in the examples and comparative examples. [Diagram 2] FIG. 2 is a schematic diagram showing a cross-sectional structure near the bottom of a crucible of a gas atomizing device used in Examples and Comparative Examples. [Diagram 3] FIG. 2 is a diagram showing a schematic configuration of a sputtering film forming apparatus used in the examples. [Figure 4] FIG. 4 is a diagram showing a schematic configuration of the inside of a film formation chamber 51 of the sputtering film formation apparatus shown in FIG. [Diagram 5] 2 is a graph showing the photoelectron peak spectra of Mg and Fe at etching times of 0 seconds and 600 seconds measured by X-ray photoelectron spectroscopy for the Sm-Fe-N magnetic powder obtained in Example 1. [Figure 6] FIG. 1 is a diagram illustrating an example of a HAADF (high angle annular dark field) image observed by a STEM (scanning transmission electron microscope) of powder particles after heating the Sm-Fe-N magnetic powder obtained in Example 1 in air at 300° C. for 120 minutes. [Figure 7]7 is a graph illustrating the element concentration profiles of O, Fe, and Al measured along the line segment AB shown in FIG. 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Sm-Fe-N magnetic particles] The Sm (samarium)-Fe (iron)-N (nitrogen) magnetic powder of the present invention is composed of Sm-Fe-N magnetic particles having a coating layer made of an alloy of Al (aluminum) and an alkaline earth metal on the surface of the particles of the Sm-Fe-N magnetic material.The Sm-Fe-N magnetic particles can be said to be particles with a so-called core-shell structure, with the part of the Sm-Fe-N magnetic material as the core and the part of the coating layer as the shell.

[0014] [Magnetic material] The magnetic material corresponding to the core of the Sm-Fe-N magnetic particles is Th 2 Zinc 17 Sm 2 Fe 17 It is mainly composed of a magnetic phase in which N (nitrogen) atoms are introduced into the crystal lattice. N atoms are Sm 2 Fe 17 It is believed that the N atoms are interstitial in the crystal lattice, and the Th 2 Zinc 17 The crystal structure of Sm is maintained. 2 Fe 17 When N atoms are introduced into the Sm-Fe-N system, the crystal magnetic anisotropy changes from in-plane to uniaxial and the Curie point rises, making it a practical magnet material. 2 Fe 17 N 3 The Sm / Fe molar ratio, which means the molar ratio of Sm to Fe, and the N / Fe molar ratio, which means the molar ratio of N to Fe, are 2 Fe 17 N 3 The closer to the stoichiometric composition, the more advantageous the magnetic properties are, but hard magnetism is also exhibited in the surrounding composition range. 2 Fe 17 N3 The stoichiometric Sm / Fe molar ratio is 0.118, and the N / Fe molar ratio is 0.176. In the Sm-Fe-N magnetic material of the present invention, it is preferable that the composition is adjusted so that the Sm / Fe molar ratio is in the range of 0.09 to 0.25 and the N / Fe molar ratio is in the range of 0.06 to 0.30, taking into consideration that an effective coercive force as a material for a bonded magnet can be stably obtained in a temperature range including room temperature. Since Sm, Fe, and N are not used as constituent elements of the coating layer, it is preferable that the Sm / Fe molar ratio and N / Fe molar ratio are also in the above ranges for the composition of the Sm-Fe-N magnetic powder of the present invention, which contains the constituent elements of the magnetic material and the coating layer. Note that the magnetic material corresponding to the core contains Sm, which contains N. 2 Fe 17 In addition to the phase, e.g. TbCu 7 SmFe with the type crystal structure 7 In some cases, different phases such as a cyclic phase and a cyclic phase may be present, but the presence of different phases is permitted as long as it does not impede the object of the present invention.

[0015] [Coating layer] The coating layer, which corresponds to the shell of the Sm-Fe-N magnetic particles, is made of an alloy of Al and an alkaline earth metal. In this specification, the alkaline earth metal element is represented as Ae, and the alloy of Al and an alkaline earth metal is represented as an "Al-Ae alloy". Here, Ae in the Al-Ae alloy means one or more alkaline earth metal elements. Representative Al-Ae alloys include Al-Mg (magnesium) alloys, Al-Ca (calcium) alloys, and Al-Mg-Ca alloys. The Sm-Fe-N magnetic powder made of particles having an Al-Ae alloy coating layer exhibits a performance in which the problem of a decrease in coercivity after heating at about 300°C in air is significantly suppressed, that is, excellent resistance to decrease in coercivity. The reason for this is that the coating layer made of the Al-Ae alloy functions as a barrier layer that prevents oxygen from penetrating from the outside into the part of the Sm-Fe-N magnetic material that corresponds to the core when the Sm-Fe-N magnetic powder is heated in an oxidizing gas such as air to, for example, about 300°C. The composition of the Al-Ae alloy may be set, for example, in the range of 0.05 to 0.95 in terms of the Ae / (Al+Ae) molar ratio, depending on the type of alkaline earth metal element used, and may be controlled in the range of 0.20 to 0.60 or 0.25 to 0.50. The appropriate Al-Ae alloy composition depending on the type of alkaline earth metal element can be set, for example, by conducting preliminary experiments with several compositions.

[0016] As described later, the coating layer can be formed by, for example, a sputtering film formation method. The coating layer in the state after the film formation improves the coercivity decrease resistance, but the coercivity decrease resistance can be further improved by carrying out the densification heat treatment described later. In consideration of carrying out the densification heat treatment efficiently in a short time, the composition of the Al-Ae alloy is preferably adjusted to a composition range in which the melting start temperature is approximately 600°C or less. From this viewpoint, for example, when an Al-Mg binary alloy is adopted, a preferable composition range can be exemplified by a Mg / (Al+Mg) molar ratio of 0.10 to 0.95, and for example, when an Al-Ca binary alloy is adopted, a preferable composition range can be exemplified by a Ca / (Al+Ca) molar ratio of 0.35 to 0.90.

[0017] By using a powder sputtering deposition device capable of performing sputtering deposition on the particle surface while stirring the powder particles, the entire surface of the core particle can be covered with a coating layer with a high uniformity of thickness. Such a coating layer with high uniformity is considered to exhibit excellent resistance to coercivity degradation when heated at about 300°C in air by ensuring an average thickness of, for example, 10 nm or more. It is more preferable to set the deposition conditions so that the average thickness of the coating layer is in the range of 20 nm to 100 nm. The thickness of the coating layer can be confirmed, for example, by a HAADF (high angle annular dark field) image of the particle observed by a STEM (scanning transmission electron microscope).

[0018] The amount of the coating layer can also be grasped from the chemical composition and particle size of the powder. For example, the ratio of the total amount of Al and alkaline earth metal element Ae, which are the constituent elements of the coating layer, to Fe, which is the constituent element of the magnetic particle corresponding to the core, i.e., the (Al+Ae) / Fe molar ratio, is an index showing the quantitative ratio of the coating layer to the powder particle. In addition, if the (Al+Ae) / Fe molar ratio is the same, it is considered that the average thickness of the coating layer increases as the particle size increases. It is preferable that the amount of the coating layer is adjusted to an effective range according to the particle size. As a result of various studies, in the Sm-Fe-N magnetic powder of the present invention, the coating amount index R expressed by the following formula (1) is preferably 0.10 μm or more and 2.00 μm or less, and the coating amount index R of 0.10 μm or more and 1.00 μm or less is particularly preferable in terms of the balance between heat resistance and cost. Coverage index R=[(Al+Ae) / Fe]×D 50 …(1) Here, the (Al+Ae) / Fe molar ratio in the powder having an Al-Ae alloy coating layer is substituted for [(Al+Ae) / Fe] in formula (1), and D 50 The cumulative 50% particle diameter D 50 The value in μm is assigned.

[0019] [Particle size] Considering that the Sm-Fe-N magnetic powder of the present invention is used as a magnetic material for bonded magnets, the cumulative 50% particle diameter D 50 It is preferable that the thickness is 0.5 μm or more and 5.0 μm or less.

[0020] [Heat resistance of Sm-Fe-N magnetic powder] In the case of Sm-Fe-N magnetic powder for use in bonded magnets that use engineering plastics (such as the above-mentioned SPS resin and PPS resin) as a binder and have high heat resistance and strength, in order to make such bonded magnets fully adaptable to the mass production process, when the powder is subjected to a heating test in which it is held in air at 300°C for 120 minutes, the coercive force reduction rate ΔH expressed by the following formula (2) is c It is preferable that the coercive force reduction rate ΔH is 60% or less. c It is more preferable that the coercive force reduction rate ΔH is 45% or less, and further preferably 35% or less. c The lower limit of ΔH is not particularly limited, but it is possible to manufacture the film without excessive process load. c An example of the range is 15% or more. δH c =100×(H c0 -H c1 ) / H c0 …(2) Here, H c0 is the coercive force (kA / m) of the powder before the heating test, H c1 is the coercive force (kA / m) of the powder after the heating test.

[0021] [Film forming process] As the Sm-Fe-N magnetic powder, which is the material to be coated, those obtained by using known synthesis methods such as reduction diffusion method and gas atomization method can be applied. For the coating layer, a vapor phase growth method can be suitably used as a coating method that is unlikely to cause thermal damage to the Sm-Fe-N magnetic material and can form a coating of an Al-Ae alloy of any composition. As a specific embodiment, for example, as shown in the examples described later, a method can be mentioned in which a coating layer of an Al-Ae alloy is formed on the surface of the particles constituting the Sm-Fe-N magnetic powder, which is the material to be coated, is stirred and flowed in a sputtering coating device. Here, "stirring and flowing" refers to an operation of applying a stirring force to the powder contained in the coating device to flow the powder particles. By this operation, the powder particles can be continuously circulated so that each particle is evenly exposed to the space where the atoms to be coated are present. By applying such a film-forming method, the surface of the magnetic particles corresponding to the core can be covered with a film of an Al-Ae alloy, and as a result, a remarkable improvement effect in heat resistance is exhibited. Note that the film-forming method of the coating layer is not limited to a vapor phase growth method such as a sputtering film-forming method, and if it is confirmed that an Al-Ae alloy film with high uniformity in thickness can be formed on the surface of the powder particles without thermally damaging the magnetic body, it is considered possible to apply other known film-forming techniques or newly developed film-forming techniques.

[0022] [Densification process] In the case of Al-Ae alloys, depending on the type of alkaline earth metal used, it may be possible to find a composition range where the melting start temperature is low, for example, below 600°C. In such a composition range where the melting start temperature is low, the crystal structure of the Sm-Fe-N magnetic material (Th with N introduced) is formed on the Sm-Fe-N magnetic powder after the Al-Ae alloy coating layer has been formed. 2 Zinc 17By carrying out a heat treatment in which the material is heated to a temperature range of, for example, 550°C or less where the mold structure does not decompose, diffusion involving a liquid phase or solid phase diffusion in the coating layer progresses rapidly, and the coating layer can be densified. This densification treatment can further improve the resistance to coercivity degradation when heated at about 300°C in air. Therefore, this densification treatment can be carried out as necessary.

[0023] Specifically, in the above-mentioned film formation process, the melting start temperature T M The Sm-Fe-N magnetic powder is provided with an Al-Ae alloy coating layer having a melting temperature T M can be known from, for example, the equilibrium phase diagram of an Al-Ae alloy. Next, the Sm-Fe-N magnetic powder obtained in the film formation process is heated in a non-oxidizing atmosphere such as Ar (argon) gas to a temperature T (° C.) that satisfies the following formula (3). T M (℃)-100≦T(℃)≦550 …(3) The heating temperature T is the melting start temperature T M If the temperature is above the melting temperature T, the Al-Ae alloy coating layer will enter the solid-liquid coexistence region and will begin to melt partially. In this case, the coating layer will rapidly become dense due to diffusion involving the liquid phase. On the other hand, if the heating temperature T is higher than the melting start temperature T M If the temperature is lower than this, the coating layer will become denser due to solid-state diffusion. M In order to rapidly promote diffusion, it is advantageous to raise the temperature to a temperature close to the "T M (℃)-100" as shown in the figure. M The densification can be efficiently achieved by raising the temperature to a temperature where the difference between the heating temperature T and T is within 100°C. M If greater than or equal to T M In both cases, the crystal structure of the Sm-Fe-N magnetic material (Th 2 Zinc 17In order to prevent decomposition of the mold structure, the heating temperature T must be set in the range of 550°C or less, and is preferably set in the range of 520°C or less. The holding time at the heating temperature T (°C) may be set, for example, in the range of 0 seconds or more and 3600 seconds or less. Here, a holding time of 0 seconds at the heating temperature T (°C) means a heat pattern in which the material temperature starts to decrease immediately after it reaches T (°C).

[0024] In addition, the melting start temperature T M Even when a coating layer having an Al-Ae alloy composition range where the melting temperature T exceeds 600°C is formed, a densification treatment can be performed by heating to a temperature range of 550°C or less. M Al-Ae alloys with melting temperature T M For Sm-Fe-N magnetic powders having any coating layer formed of Al-Ae alloys with a temperature exceeding 600°C, it is effective to perform a densification treatment in which the temperature is raised to a temperature T (°C) that satisfies the following formula (4) in a non-oxidizing atmosphere such as Ar (argon) gas. 450≦T(℃)≦550 …(4) In this case as well, the holding time at the heating temperature T (° C.) may be set within the range of, for example, 0 seconds or more and 3600 seconds or less. The melting start temperature T M In the case of Sm-Fe-N magnetic powder having an Al-Ae alloy coating layer with a heating temperature of 600° C. or less, it is more preferable to control the heating temperature T to satisfy the formula (3) as described above.

[0025] [Example of a method for manufacturing Sm-Fe-N magnetic powder, which is a film-forming material] As mentioned above, synthesis methods such as the reduction diffusion method and the gas atomization method can be used to manufacture the Sm-Fe-N magnetic powder, which is the material to be deposited. The process using the gas atomization method has the advantage of not causing an environmental burden due to alkaline waste liquid. A typical process using this gas atomization method is a method in which the steps of gas atomization, heat treatment, pulverization, and nitriding are carried out in the order mentioned above. Before the pulverization, hydrogen treatment can be carried out as necessary. The applicant disclosed the above process technology in detail in Japanese Patent Application No. 2023-061046. Each step will be briefly described below.

[0026] (Gas atomization) As the metal raw material for generating the molten metal to be subjected to gas atomization, a Sm-Fe based master alloy, metallic Sm, metallic Fe, etc., whose composition is known and which has been melted in advance, can be used. The composition of the molten metal is Sm 2 Fe 17 It is desirable to adjust the Sm / Fe molar ratio to a value relatively close to the stoichiometric composition, specifically, to a range of 0.09 to 0.25. Although the inclusion of metal elements other than Sm and Fe is permitted to the extent that it does not impair the required properties of the magnetic powder finally obtained, the total content of Sm and Fe in the molten metal is preferably 95.0 mass% or more, and more preferably 98.0 mass% or more. It is desirable to generate the molten metal in an inert gas atmosphere other than nitrogen or in a vacuum.

[0027] The molten metal, which has been kept at a specified temperature and made sufficiently homogenous, is discharged from the nozzle into the gas space, and cooling gas is forcefully sprayed onto the molten metal immediately after it is discharged. This causes the molten metal to turn into fine liquid phase particles, which fly through the gas space and solidify. The temperature of the molten metal at the time of discharge may be set within the range of 1400 to 1900°C. It is desirable that the pressurizing gas for discharging the molten metal, the injection gas sprayed onto the molten metal, and the atmospheric gas in the gas space in which the liquid phase particles fly are all inert gases other than nitrogen. The particle size of gas atomized powder is determined by the cumulative 50% particle diameter D in the volumetric particle size distribution determined by the laser diffraction and scattering method. 50 For example, the particle size of the gas atomized powder is preferably 70.0 μm or less, more preferably 50.0 μm or less, and even more preferably 25.0 μm or less. There is no particular lower limit for the particle size of the gas atomized powder, but the above D 50 It is sufficient to adjust the thickness to be in the range of 5.0 μm or more, and it may be controlled to be in the range of 10.0 μm or more.

[0028] (Heat treatment) In the heat treatment step, the gas atomized powder of Sm-Fe alloy is heat-treated at a high temperature to coarsen the crystal grains. Specifically, by heating to 900°C or higher, the crystal grains can be coarsened to a size where the average crystal grain size in the equivalent circle diameter in the cross-sectional structure of the particles is, for example, about 3 to 15 μm. This coarsening of the crystal grains makes it easier for intragranular fracture to occur in the crushing in the subsequent step, making it easier to obtain fine Sm-Fe alloy powder with a high ratio of particles consisting of single crystal grains. It is more preferable to heat to 930°C or higher. Since excessive heating is uneconomical, the heating temperature is preferably set in the range of 1200°C or lower, and may be controlled to 1100°C or lower, or 1000°C or lower. The holding time in the temperature range of 900°C to 1200°C can be, for example, 10 seconds to 10 minutes, and may be set in the range of 30 seconds to 5 minutes. The heating atmosphere is preferably an inert gas atmosphere other than nitrogen, or a vacuum.

[0029] (Hydrogen processing) In order to facilitate intragranular fracture in the subsequent crushing process, it is effective to perform hydrogen treatment by heating in a hydrogen gas atmosphere before crushing. Hydrogen penetrates into the crystal grains of the Sm-Fe alloy by hydrogen treatment, and intragranular fracture becomes more likely to occur due to the phenomenon of so-called hydrogen embrittlement. Therefore, hydrogen treatment can be performed as necessary. The heating temperature for hydrogen treatment is preferably set in the range of 200°C to 600°C, and the holding time in that temperature range may be set in the range of, for example, 30 minutes to 600 minutes.

[0030] (Crushing) When mechanically pulverizing the powder of Sm-Fe alloy with coarsened crystal grains by the above heat treatment, the individual particles are broken by fracture at the grain boundaries (intergranular fracture) as well as fracture within the grains (intracegranular fracture). When the powder particles are refined by such "fracture including intragranular fracture", fine Sm-Fe alloy powder with a high proportion of particles consisting of single crystal grains can be obtained. For example, a wet ball mill can be used as a pulverizing method. The particle size after pulverization is determined by the cumulative 50% particle size D in the volume-based particle size distribution determined by the laser diffraction / scattering method. 50 It is preferable to adjust the particle diameter D to 5.0 μm or less, and more preferably to 3.0 μm or less. If the particle diameter is made too fine, the crystal lattice distortion increases due to the application of an excessive external force, which may adversely affect the magnetic properties. 50 It is preferable to carry out the pulverization so that the particle size becomes 0.5 μm or more, and it is also possible to carry out the pulverization so that the particle size becomes 1.0 μm or more.

[0031] (nitriding) Next, a nitriding treatment is carried out to obtain Sm-Fe-N magnetic powder. The nitriding treatment can be carried out by heating and holding the Sm-Fe alloy powder finely pulverized by the above-mentioned pulverization in a non-oxidizing gas atmosphere containing a nitrogen compound or nitrogen. If the heating temperature is too high, Sm 2 Fe 17 Nitrogen atoms have entered the crystal. 2 Fe 17 N 3 The structure based on nitriding becomes unstable, making nitriding difficult. The heating temperature for nitriding is preferably 500°C or lower. If the temperature is too low, it takes a long time for nitriding to proceed, which is disadvantageous in terms of diffusing nitrogen atoms uniformly to the inside of the particles. A heating temperature of 300°C or higher is effective. The atmospheric gas for nitriding is ammonia (NH 3 ) and hydrogen (H 2 For example, a mixture of ammonia and hydrogen in a ratio of NH 3 :H 2The ratio can be in the range of 10:90 to 60:40. Other atmospheric gases used in the nitriding treatment include hydrogen, ammonia and nitrogen (N 2 Examples of the non-oxidizing atmosphere include a mixture of hydrogen, ammonia, and argon (Ar), ammonia alone, ammonia and nitrogen, ammonia and argon, nitrogen alone, and nitrogen and hydrogen. The optimal time for the nitriding treatment varies somewhat depending on the average particle size of the powder, the composition of the atmospheric gas, and the temperature, but the optimal time is usually found in the range of 15 to 240 minutes. This nitriding process removes Sm 2 Fe 17 Nitrogen is introduced into the crystals, and an Sm-Fe-N magnetic powder having an N / Fe molar ratio in the range of 0.06 to 0.30 is obtained, which exhibits excellent magnetic properties. EXAMPLES

[0032] In the following examples, elemental analysis, powder particle size distribution measurement, powder magnetic measurement, and X-ray diffraction measurement were performed by the following methods.

[0033] (Elemental analysis) Metal element analysis was performed by heating and dissolving the analytical sample in hydrochloric acid in a glove box filled with argon (Ar) gas, then diluting it to prepare a sample solution for analysis, and analyzing this solution using an ICP optical emission spectrometer (Agilent 720, manufactured by Agilent Technologies). Nitrogen analysis was performed by the inert gas fusion-thermal conductivity method using an oxygen / nitrogen analyzer (Horiba, EMGA-920).

[0034] (Particle size distribution measurement of powder) The cumulative 50% particle diameter D in the volume-based particle size distribution was measured using a laser diffraction particle size distribution analyzer (Sympatec, Helos / Rodos). 50 asked for.

[0035] (Magnetic measurement of powder) A sample cell filled with 20 mg of sample powder and paraffin was placed at the center of the electromagnet, and the sample cell was heated to 80°C for 2 minutes using a hot air generator. The amount of paraffin filled here was the amount that filled the container of the sample cell with the sample powder and paraffin. Next, while still heated at 80°C, an external magnetic field of 1.0 T (tesla) was applied to the sample cell by the electromagnet for 2 minutes. Next, the sample cell was cooled to room temperature while still applying the magnetic field of 1.0 T. In this way, a magnetically oriented measurement sample was obtained. This measurement sample was placed in a VSM (VSM-5HSC, manufactured by Toei Kogyo Co., Ltd.) so that the direction of the applied magnetic field was parallel to the magnetic field orientation direction of the measurement sample, and the coercive force H c The measurement conditions were a maximum applied magnetic field of 4.79 MA / m and a sweep rate of 8 kA / m sec.

[0036] (X-ray diffraction measurement) The X-ray diffraction patterns of the powder samples were measured using Co-Kα radiation at a tube voltage of 45 kV and a tube current of 40 mA.

[0037] [Example 1] (Synthesis of Sm-Fe powder by gas atomization method) FIG. 1 shows a schematic diagram of the gas atomizing device used in this example. There are two independent spaces, an upper space and an lower space, in the chamber, which can be evacuated by a vacuum exhaust device 10, and these spaces can be turned into gas phase spaces having a predetermined gas atmosphere by introducing gas from atmospheric gas supply sources 11a and 11b. The upper space contains a crucible 1, in which raw materials are melted by induction heating with a high-frequency coil 4 to form a molten metal 5. A molten metal discharge nozzle member 2 is attached to the bottom of the crucible 1 for discharging the molten metal 5 into the gas phase space below. The molten metal flow path is blocked by pressing a stopper 3 against the molten metal discharge nozzle member 2 until the molten metal 5 is discharged. After the molten metal 5 is sufficiently homogenized and a predetermined temperature is obtained, the stopper 3 is raised while gas is supplied at a predetermined pressure from the gas supply device 13 for discharging the molten metal to the surface of the molten metal in the crucible 1, and the molten metal 5 is discharged from the tip of the nozzle member 2 for discharging the molten metal to the gas space at the bottom. The gas space at the bottom is equipped with a gas injection nozzle 6 for blowing gas onto the discharged molten metal 5. Before the start of discharging, the gas supply device 12 starts to supply gas to the gas injection nozzle 6, and the gas is injected from the gas injection nozzle 6 at high pressure. By applying a strong jet of the injected gas to the molten metal 5, fine particles of the molten metal 5 are formed, and the fine particles are rapidly cooled and solidified. The solidified metal particles 7 are deposited at the bottom of the gas space at the bottom.

[0038] FIG. 2 shows a schematic diagram of an example of the cross-sectional structure near the bottom of the crucible of a gas atomizing device. The molten metal discharge nozzle member 2 attached to the bottom of the crucible 1 has a discharge port 21 which is an opening at the tip of the nozzle, and a stopper abutment surface 22. The stopper 3 is movable in the vertical direction, and has the function of blocking the nozzle flow path by abutting against the stopper abutment surface 22 of the molten metal discharge nozzle member 2, and opening the nozzle flow path by moving away from the stopper abutment surface 22 when the molten metal is discharged. In this example, the entire crucible 1 is made of boron nitride (BN), the entire molten metal discharge nozzle member 2 is made of boron nitride (BN), and at least the entire portion of the stopper 3 which is to be immersed in the molten metal 5 is made of yttrium oxide (Y 2 O 3The inner diameter of the molten metal discharge nozzle member 2 was 3.0 mm.

[0039] As the raw material, a pre-melted Sm-Fe alloy was used. As a result of elemental analysis, the Sm / Fe molar ratio of this raw material alloy was 0.16. 996.7 g of this raw material was placed in a crucible and melted by high-frequency induction heating in an Ar atmosphere. After the raw material alloy was completely melted, 27 minutes after the start of heating, the entire amount of 1637°C molten metal was discharged from the nozzle into the lower gas phase space. The maximum supply pressure of the gas for discharging the molten metal was 65 kPa in terms of the pressure difference with the atmospheric gas pressure. Ar was used as the injection gas. The lower gas phase space was also in an Ar atmosphere. The generated powder was collected and small particles were removed using a 16 μm mesh sieve in a glove box under a nitrogen atmosphere. In this way, gas atomized powder was obtained. Elemental analysis of the gas atomized powder revealed that the Sm / Fe molar ratio was 0.16, which was equivalent to that of the raw alloy. In addition, the cumulative 50% particle diameter D 50 was 22.8 μm.

[0040] (Heat treatment) The heat treatment furnace used was an electrically heated tubular furnace connected to a glove box filled with argon (Ar) gas. The Sm-Fe gas-atomized powder was placed in a sealed container filled with argon gas, transferred to the glove box, and loaded into the tubular furnace without being exposed to the atmosphere. The tubular furnace was heated from room temperature to 950°C at a rate of 150°C / min while flowing argon gas, and then held at 950°C for 1 minute, and then cooled to 50°C or less while flowing argon gas to obtain a heat-treated powder.

[0041] (Hydrogen processing) The heat-treated powder obtained was transferred to another tube furnace and heated with hydrogen (H 2 The temperature was raised to 300°C at a rate of 10°C / min while flowing hydrogen gas, and then held at 300°C for 180 minutes. Next, the temperature was cooled to below 50°C while still flowing hydrogen gas, and the atmosphere in the furnace was replaced with argon gas. In this way, hydrogen-treated powder was obtained.

[0042] (Crushing) The obtained hydrogen-treated powder was placed in an airtight container filled with argon gas and transferred from the tubular furnace to another glove box filled with argon gas. In the glove box to which the powder was transferred, grinding was performed using a wet ball mill. 5.0 g of hydrogen-treated powder, 250 g of stainless steel balls with a diameter of 2.5 mm, and acetonitrile as a solvent were placed in a stainless steel mill pot with a capacity of 240 mL. The amount of acetonitrile was set to the minimum amount that all the stainless steel balls were immersed in acetonitrile. Next, the mill pot containing the hydrogen-treated powder was placed on a ball mill rotating stand (manufactured by Asahi Rika Seisakusho, AV-1 type), and grinding was performed at a rotation speed of 120 rpm and an operating time of 2 hours. Next, the contents in the mill pot were passed through a sieve to remove the stainless steel balls on the sieve, and the slurry that passed through the sieve was collected. Next, the collected slurry was left to stand, the supernatant liquid was discarded, and the remaining slurry was vacuum dried to obtain a ground powder. The above operations from grinding to drying were performed in a glove box with an argon gas atmosphere.

[0043] (nitriding) The ground powder obtained as described above was transferred to an electrically heated tubular furnace under an argon gas atmosphere, and then ammonia (NH 3 ) gas 35% by volume, hydrogen (H 2 A mixed gas of 65% by volume of H 2 O 3 was then flowed to replace the gas in the tubular furnace. After that, while flowing the mixed gas, the temperature was raised to 420°C at a rate of 5°C / min, and the temperature was held at 420°C for 30 minutes to perform nitriding treatment. Next, the gas flowing in the tubular furnace was changed to hydrogen (H 2 ) gas and held at 420°C for another 120 minutes, then the gas flowing in the tubular furnace was changed to argon gas and held at 420°C for 90 minutes. After that, heating was stopped and the material was cooled to near room temperature while flowing argon gas, to obtain nitrided powder.

[0044] (Washing and crushing) Next, the obtained nitrided powder was transferred from the tubular furnace into a glove box filled with argon gas, then placed in a 20 mL screw-capped glass bottle, and 15 mL of heptane was added as a solvent. Next, the glass bottle was placed in an ultrasonic disperser (UH-150 model, manufactured by SMT Corporation) and operated for 100 minutes with an output condition of 20 kHz, 0.3 seconds transmission, and 0.7 seconds off. Next, the supernatant in the glass bottle was removed, and the remaining heptane was removed by vacuum drying to obtain Sm-Fe-N magnetic powder. The obtained Sm-Fe-N magnetic powder was measured by X-ray diffraction and found to be 2 Zinc 17 It was confirmed that this Sm-Fe-N magnetic powder has a crystalline structure. The cumulative 50% particle diameter D 50 was 1.8 μm.

[0045] (film formation) The Sm-Fe-N magnetic powder obtained as described above was used as a film-forming material, and a coating layer of Al-Mg alloy was formed on the surface of the powder particles by a sputtering film-forming method. The film-forming method will be described below.

[0046] FIG. 3 shows a schematic diagram of the sputtering deposition apparatus used in this example. The figure on the left corresponds to a side view, and the figure on the right corresponds to a front view. The deposition chamber 51 of the sputtering deposition apparatus body is connected to a narrow glove box 52 filled with argon gas on the front side, and sample powder can be manually introduced into the deposition chamber 51 through a glove port 53. A sliding door is installed between the deposition chamber 51 and the glove box 52, and can be opened and closed from inside the glove box 52. By closing the door, the deposition chamber 51 can be evacuated to a vacuum while the glove box 52 side is filled with argon gas. Two sputter cathodes 54 are installed at the top of the deposition chamber 51.

[0047] FIG. 4 shows a schematic diagram of the internal configuration of the film-forming chamber 51 of the sputtering film-forming apparatus shown in FIG. 3. The hatched portion in FIG. 4 shows a cross-sectional shape in a plane including the rotation axis of the stepping motor 57. This film-forming apparatus is equipped with two sputtering cathodes 54, so that two types of targets can be used for co-sputtering. In this example, one sputtering cathode 54 is equipped with metal Al, and the other sputtering cathode 54 is equipped with metal Mg as a target material. Each target material is a disk shape with a thickness of 5 mm and a diameter of 2 inches. Magnetron sputtering is possible by the magnetic field generated by the neodymium magnet built into the back position of the target material. A powder storage container 55 with a circular bottom with a diameter of 65 mm is installed at the focal position of the two cathodes, and a stirring rod 56 is inserted into the powder storage container 55. The powder storage container 55 is connected to a stepping motor 57 installed below the film formation chamber 51, and the sample powder, which is the material to be film-formed, can be continuously stirred and flowed by rotating the powder storage container 55 while it is held in the powder storage container 55. By using this sputtering film formation device, the sample powder can be automatically and continuously stirred and flowed while sputtering film formation is performed, so that the surfaces of the powder particles can be coated with elements of the target material attached to the sputtering cathode 54.

[0048] The Sm-Fe-N magnetic powder, which is the material to be deposited, was transferred into the glove box 52 while being kept under an argon gas atmosphere. The sliding door at the connection part with the deposition chamber 51 was opened, and 10 g of Sm-Fe-N magnetic powder was charged into the powder storage container 55 under an argon gas atmosphere. The sliding door was then closed to seal the deposition chamber 51. The deposition chamber 51 was temporarily filled with approximately 1×10 -3After evacuating to 1000 Pa, argon process gas was introduced into the film-forming chamber 51, and the flow rate of argon was adjusted so that the argon gas pressure in the film-forming chamber 51 was maintained at about 0.5 Pa. While continuously stirring the Sm-Fe-N magnetic powder, which is the material to be film-formed, by rotating the powder storage container 55 at 50 rpm, two sputtering cathodes 54 were used to perform binary co-sputtering of Al and Mg, and the surface of the powder particles was coated with an Al-Mg alloy. At this time, the film-forming time was adjusted so that the average film thickness of the coating layer was about 50 nm. In this example, a coating layer with a molar ratio of Al to Mg of 54:46 was formed by adjusting the output ratio of both sputtering cathodes.

[0049] (Densification treatment) The Sm-Fe-N magnetic powder after the film formation was transferred to a heat treatment furnace while being kept in an argon gas atmosphere, and was subjected to heat treatment at 500 °C for 1 minute in an argon atmosphere. For an Al-Mg alloy with a composition in which the molar ratio of Al to Mg is about 54:46, the melting start temperature T M Since the temperature at which the Al-Mg alloy coating layer is formed is thought to be around 450°C, it is presumed that the Al-Mg alloy coating layer entered a solid-liquid coexistence region when heated to 500°C and was rapidly densified. The Sm-Fe-N magnetic powder that had been subjected to this densification treatment was used as the test powder in this example and was subjected to the following investigation.

[0050] (X-ray photoelectron spectroscopy measurement) For the test powder in this example, the element distribution near the particle surface was measured using an X-ray photoelectron spectrometer (ULVAC-PHI, PHI-5000 VersaProbeII) by the following method. Al-Kα rays (1486.6 eV) were used as the X-ray source, and the energy of the emitted photoelectrons was analyzed by a hemispherical electron analyzer with a pass energy of 23.5 eV and an energy interval of 0.1 eV. In addition, as a depth profile analysis, the distribution in the depth direction from the surface was evaluated by alternately repeating etching of the sample surface by Ar sputtering and measurement. The acceleration voltage of Ar ions was 2 kV. The etching depth corresponding to an etching time of 600 seconds was 1.0 Å for Fe. 2 O 3 This is estimated to be approximately 43nm.

[0051] Figure 5 shows the Mg (magnesium) 2p level and Fe (iron) 2p level measured by X-ray photoelectron spectroscopy. 3 / 2 The photoelectron peaks of the Fe SiO2 and Fe SiO2 levels were measured after etching for 0 seconds (i.e., the outermost surface) and 600 seconds (i.e., Fe 2 O 3 The spectrum at a conversion depth of approximately 43 nm is shown. At an etching time of 0 seconds, a significant peak intensity of Mg was observed, but no significant peak intensity of Fe was observed. On the other hand, at an etching time of 600 seconds, the peak intensity of Mg dropped significantly, and a significant peak intensity of Fe was observed. From this, it can be evaluated that the surfaces of the test powder particles in this example are covered with a coating layer formed by the above-mentioned film formation to the extent that the exposure of the base (the Sm-Fe-N magnetic part corresponding to the core) cannot be confirmed.

[0052] (composition) The test powder was subjected to elemental analysis using the above-mentioned analytical method. The results are shown in Table 1 (the same applies to the following examples). The test powder in this example had a Sm / Fe molar ratio of 0.16, a N / Fe molar ratio of 0.22, and a (Al+Ae) / Fe molar ratio of 0.23.

[0053] (particle size distribution) The particle size distribution of the test powder was measured by the method described above. As a result, the test powder in this example had a cumulative 50% particle diameter D 50 was 1.9 μm.

[0054] (Coverage index R) The coating amount index R of the test powder was calculated using the above formula (1). As a result, the coating amount index R of the test powder in this example was 0.43 μm.

[0055] (Coercive force) The magnetic properties of the test powder were measured using the method described above. As a result, the coercive force H c was 1060 kA / m (13.3 kOe).

[0056] (Evaluation of heat resistance) 0.1 g of the test powder sample was placed on a stainless steel tray and placed in a constant temperature dryer (DRA-630DB, manufactured by ADVANTEC) heated to 300°C, and subjected to a heating test in which the sample was heated and held at 300°C for 120 minutes in an atmospheric environment (i.e., in air). The stainless steel tray was then removed from the constant temperature dryer, and the powder sample was allowed to cool in air at room temperature. After this heating test, magnetic measurements were performed on the powder sample using the same method as above, and the coercive force H after the heating test was 1.0 g. c was 780 kA / m (9.8 kOe). The coercive force loss rate δH c was calculated using the following formula (2). δH c =100×(H c0 -H c1 ) / H c0 …(2) Here, H c0 is the coercive force (kA / m) of the powder before the heating test, H c1 is the coercive force (kA / m) of the powder after the heating test. The coercive force reduction rate δH of the test powder in this example c was 100 × (1060-780) / 1060 ≒ 26.4%.

[0057] Figure 6 shows an example of a high-angle annular dark field (HAADF) image observed by a scanning transmission electron microscope (STEM) for the particles that make up the test powder in this example after a heating test at 300°C for 120 minutes in air. The white part is the Sm-Fe-N magnetic material part that corresponds to the core, and the gray part along the outline is the coating layer. Fig. 7 illustrates element concentration profiles of O (oxygen), Fe (iron), and Al (aluminum) measured by EDS (energy dispersive X-ray spectroscopy) line analysis along the line segment AB shown in Fig. 6. The part where the Al concentration is high at a distance of about 0.27 µm from A is the position of the coating layer. It can be seen that the coating layer prevents oxygen from penetrating into the Sm-Fe-N magnetic material, which corresponds to the core. In other words, it is presumed that the coating layer according to the present invention functions as a barrier layer that prevents oxygen from penetrating when heated in the atmosphere, thereby realizing excellent resistance to coercivity degradation.

[0058] [Example 2] In this example, the characteristics of a Sm-Fe-N magnetic powder coated with an Al-Mg alloy that had not been subjected to a densification treatment were examined as a test powder. Specifically, a Sm-Fe-N magnetic powder was obtained through the steps of gas atomization, heat treatment, pulverization, hydrogen treatment, nitriding, washing, and film formation under the same conditions as in Example 1. This powder (corresponding to the powder before the densification treatment in Example 1) was used as a test powder and elemental analysis, particle size distribution measurement, magnetic measurement, and heat resistance evaluation were performed using the same methods as described above.

[0059] The properties of the test powder in this example were as follows: The Sm / Fe molar ratio was 0.17, the N / Fe molar ratio was 0.23, and the (Al+Ae) / Fe molar ratio was 0.23. The cumulative 50% particle diameter D 50 The thickness of the coating was 2.0 μm. The coverage index R was 0.47 μm. The coercive force H c The coercive force H of the powder after a 120-minute heating test at 300°C in air was 1170 kA / m (14.7 kOe). c is 560 kA / m (7.0 kOe), and the coercive force reduction rate ΔH calculated by the above formula (2) is c was 52.1%.

[0060] [Comparative Example 1] In this example, the characteristics of a Sm-Fe-N magnetic powder coated with an Al-Mg alloy, which does not have a coating layer, were used as a test powder to examine the characteristics. Specifically, Sm-Fe-N magnetic powder was obtained through the processes of gas atomization, heat treatment, pulverization, hydrogen treatment, nitriding, and washing under the same conditions as in Example 1. This powder (corresponding to the film-forming material in Example 1) was used as a test powder and subjected to elemental analysis, particle size distribution measurement, magnetic measurement, and evaluation of heat resistance by the same methods as described above.

[0061] The properties of the test powder in this example were as follows: The Sm / Fe molar ratio was 0.17, the N / Fe molar ratio was 0.21, and the (Al+Ae) / Fe molar ratio was 0.00. The cumulative 50% particle diameter D 50 The thickness of the coating layer was 1.8 μm. Since no coating layer was formed, the coating amount index R was 0.00 μm. c The coercive force H of the powder after a 120-minute heating test at 300°C in air was 750 kA / m (9.4 kOe). c is 120 kA / m (1.5 kOe), and the coercive force reduction rate ΔH calculated by the above formula (2) is c was 84.0%.

[0062] [Example 3] (Synthesis of Sm-Fe powder by gas atomization method) A gas atomized powder was obtained in the same manner as in Example 1, except that 1700 g of Sm-Fe alloy with a Sm / Fe molar ratio of 0.15 was used as the raw material, the molten metal temperature at the time of extrusion was 1500°C, and no particle removal by sieving was performed after powder recovery. Elemental analysis of the gas atomized powder revealed that the Sm / Fe molar ratio was 0.15, which was equivalent to that of the raw alloy. In addition, the cumulative 50% particle diameter D 50 was 52.5 μm.

[0063] (Heat treatment) The heat treatment furnace used was an electrically heated tubular furnace capable of treatment under a gas atmosphere. The above-mentioned Sm-Fe gas atomized powder was placed in a sample container and loaded into the furnace, and the temperature was raised from room temperature to 990°C at a rate of 10°C / min while flowing argon gas, and then the temperature was held at 990°C for 60 minutes, and then the temperature was cooled to 50°C or less while flowing argon gas to obtain a heat-treated powder.

[0064] (Crushing) 500 g of the heat-treated powder was ground using a vibration mill (YAMP-6SND, manufactured by Euras Techno Corporation). In a glove box filled with nitrogen gas, 500 g of the heat-treated powder, 12,500 g of 3.2 mm diameter chrome steel balls, and 5.9 g of 2-propanol were placed in a 3 L stainless steel pot, sealed, and ground for 84 minutes at an amplitude of ±2.5 mm and a vibration frequency of 29.1 Hz. The ground sample was separated from the balls in the glove box filled with nitrogen gas, and the ground powder was obtained.

[0065] (nitriding) The ground powder obtained as described above was transferred to an electrically heated tubular furnace under a nitrogen gas atmosphere, and then ammonia (NH 3 ) gas 35% by volume, hydrogen (H 2 A mixed gas of 65% by volume of H 2 O 3 was then flowed to replace the gas in the furnace. Then, while flowing the mixed gas, the temperature was raised to 390°C at a rate of 5°C / min, and the temperature was held at 390°C for 260 minutes to perform nitriding treatment. Next, the gas flowing in the tubular furnace was changed to hydrogen (H 2 ) gas and held at 390°C for another 130 minutes, then the gas flowing in the tubular furnace was changed to argon gas and held at 390°C for 90 minutes. After that, heating was stopped and the material was cooled to near room temperature while flowing argon gas, obtaining Sm-Fe-N magnetic powder.

[0066] (film formation) Using the Sm-Fe-N magnetic powder obtained by the above procedure as the film-forming material, the surfaces of the powder particles were coated with an Al-Mg alloy in the same manner as in Example 1, except that the output ratio settings of both sputtering cathodes were changed and the film-forming time was adjusted so that the average film thickness of the coating layer was about 29 nm. In this example, a coating layer with an Al:Mg molar ratio of 67:33 was formed.

[0067] (Densification treatment) The Sm-Fe-N magnetic powder after the film formation was subjected to a heat treatment similar to that in Example 1 to perform a densification treatment, thereby obtaining a test powder.

[0068] The obtained Sm-Fe-N magnetic powder (sample powder) was subjected to elemental analysis, particle size distribution measurement, magnetic measurement, and evaluation of heat resistance in the same manner as in Example 1 (the same applies to each of the following examples). As a result, the Sm / Fe molar ratio was 0.14, the N / Fe molar ratio was 0.18, the (Al+Ae) / Fe molar ratio was 0.09, and the cumulative 50% particle diameter D 50 is 3.2μm, the coverage index R is 0.29μm, and the coercive force H c is 490kA / m (6.2kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 330kA / m (4.1kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 32.7%.

[0069] [Example 4] In the film-forming process, except that the film-forming time was adjusted so that the average film thickness of the coating layer was about 55 nm, a Sm-Fe-N magnetic powder (sample powder) was obtained in the same manner as in Example 3. In this example, a coating layer having an Al:Mg molar ratio of 66:34 was formed. The Sm / Fe molar ratio of this test powder was 0.14, the N / Fe molar ratio was 0.18, and the (Al+Ae) / Fe molar ratio was 0.18. The cumulative 50% particle diameter D 50 is 3.3μm, the coverage index R is 0.59μm, and the coercive force H cis 510kA / m (6.4kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 370kA / m (4.6kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 27.5%.

[0070] [Example 5] In the film-forming process, except that the film-forming time was adjusted so that the average film thickness of the coating layer was about 82 nm, a Sm-Fe-N magnetic powder (sample powder) was obtained in the same manner as in Example 3. In this example, a coating layer having an Al:Mg molar ratio of 66:34 was formed. The Sm / Fe molar ratio of this test powder was 0.13, the N / Fe molar ratio was 0.18, the (Al+Ae) / Fe molar ratio was 0.27, and the cumulative 50% particle diameter D 50 is 3.4μm, the coverage index R is 0.92μm, and the coercive force H c is 510kA / m (6.4kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 350kA / m (4.4kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 31.4%.

[0071] [Example 6] Except for changing the output ratio settings of both sputtering cathodes in the film formation process and adjusting the film formation time so that the average film thickness of the coating layer was about 53 nm, a Sm-Fe-N magnetic powder (sample powder) was obtained in the same manner as in Example 3. In this example, a coating layer with an Al:Mg molar ratio of 54:46 was formed. The Sm / Fe molar ratio of this test powder was 0.14, the N / Fe molar ratio was 0.18, and the (Al+Ae) / Fe molar ratio was 0.17. The cumulative 50% particle diameter D 50 is 3.2μm, the coverage index R is 0.54μm, and the coercive force H c is 530kA / m (6.7kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 410kA / m (5.2kOe), and the coercive force reduction rate δH calculated by the above formula (2) cwas 22.6%.

[0072] [Example 7] In the film-forming process, the film-forming time was adjusted so that the average film thickness of the coating layer was about 99 nm, and the same method as in Example 6 was used to obtain Sm-Fe-N magnetic powder (sample powder). In this example, a coating layer having an Al:Mg molar ratio of 55:45 was formed. The Sm / Fe molar ratio of this test powder was 0.14, the N / Fe molar ratio was 0.18, and the (Al+Ae) / Fe molar ratio was 0.33. The cumulative 50% particle diameter D 50 is 3.2μm, the coverage index R is 1.06μm, and the coercive force H c is 530kA / m (6.7kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 410kA / m (5.2kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 22.6%.

[0073] [Example 8] In the film-forming process, Mg was changed to Ca as the alkaline earth metal element Ae, the output ratio settings of both sputtering cathodes were changed, and the film-forming time was adjusted so that the average film thickness of the coating layer was about 45 nm. In this example, a coating layer with a molar ratio of Al and Ca of 72:28 was formed. The Sm / Fe molar ratio of this test powder was 0.14, the N / Fe molar ratio was 0.18, and the (Al+Ae) / Fe molar ratio was 0.11. The cumulative 50% particle diameter D 50 is 3.1μm, the coverage index R is 0.34μm, and the coercive force H c is 490kA / m (6.2kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 350kA / m (4.4kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 28.6%.

[0074] [Example 9] In the film-forming process, the film-forming time was adjusted so that the average film thickness of the coating layer was about 124 nm, and the same method as in Example 8 was used to obtain Sm-Fe-N magnetic powder (sample powder). In this example, a coating layer having an Al:Ca molar ratio of 72:28 was formed. The Sm / Fe molar ratio of this test powder was 0.13, the N / Fe molar ratio was 0.18, the (Al+Ae) / Fe molar ratio was 0.32, and the cumulative 50% particle diameter D 50 is 3.1μm, the coverage index R is 0.99μm, and the coercive force H c is 600kA / m (7.5kOe), coercive force H after heating test at 300℃ for 120 minutes in air c is 370kA / m (4.6kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 38.3%.

[0075] [Comparative Example 2] In this example, the film-forming process and the densification process in Example 3 were omitted to produce Sm-Fe-N magnetic powder without a coating layer, and the characteristics were investigated. That is, the test powder in this example corresponds to the Sm-Fe-N magnetic powder at the stage where the process up to the nitriding process was completed in the same manner as in Example 3. The Sm / Fe molar ratio of this test powder was 0.15, the N / Fe molar ratio was 0.19, the (Al+Ae) / Fe molar ratio was 0.00, and the cumulative 50% particle diameter D 50 is 3.0μm, the coverage index R is 0.00μm, and the coercive force H c is 590kA / m (7.4kOe), and the coercive force H after heating test at 300℃ for 120 minutes in air c is 180kA / m (2.3kOe), and the coercive force reduction rate δH calculated by the above formula (2) c was 69.5%. The above results are shown in Table 1.

[0076] [Table 1]

[0077] The Sm-Fe-N magnetic powder of the embodiment on which the Al-Ae alloy coating layer was formed had a coercive force reduction rate ΔH c was 60% or less, and the resistance to coercive force decrease was significantly improved as compared with the Sm-Fe-N magnetic powders of Comparative Examples 1 and 2 in which the coating layer was not formed. It was also confirmed that the resistance to coercivity decrease was further improved by carrying out a densification treatment (comparison between Example 1 and Example 2). [Explanation of symbols]

[0078] 1 crucible 2 Molten metal discharge nozzle parts 3 Stopper 4 High frequency coil 5 Molten metal 6 Gas injection nozzle 7 Solidified metal particles 10 Vacuum exhaust device 11a, 11b Atmospheric gas supply source 12 Injection gas supply device 13 Gas supply device for discharging molten metal 21 Discharge port 22 Stopper contact surface 51 Deposition chamber 52 Glove box 53 Groveport 54 Sputter Cathode 55 Powder container 56 Stirring rod 57 Stepping motor

Claims

1. When an alkaline earth metal element is represented as Ae, the highly heat-resistant Sm-Fe-N magnetic powder is composed of Sm-Fe-N magnetic particles having an Al-Ae alloy coating layer on the surface.

2. 2. The highly heat-resistant Sm-Fe-N magnetic powder according to claim 1, wherein the Sm / Fe molar ratio is from 0.09 to 0.25, and the N / Fe molar ratio is from 0.06 to 0.

30.

3. Cumulative 50% particle diameter D in volume-based particle size distribution by laser diffraction / scattering method 50 2. The highly heat-resistant Sm-Fe-N magnetic powder according to claim 1, wherein the surface roughness is 0.5 μm or more and 5.0 μm or less, and the coating amount index R represented by the following formula (1) is 0.10 μm or more and 2.00 μm or less. Coverage index R = [(Al + Ae) / Fe] × D 50 …(1) Here, the value of the (Al+Ae) / Fe molar ratio in the powder having an Al-Ae alloy coating layer is substituted for [(Al+Ae) / Fe] in the formula (1), and D 50 The cumulative 50% particle diameter D 50 The value of (μm) is substituted.

4. 4. The highly heat-resistant Sm-Fe-N magnetic powder according to claim 3, wherein the coating amount index R is 0.10 μm or more and 1.00 μm or less.

5. 2. The highly heat-resistant Sm-Fe-N magnetic powder according to claim 1, wherein the alkaline earth metal element Ae is one or more elements selected from the group consisting of Mg and Ca.

6. When subjected to a heating test in which the material was held in air at 300° C. for 120 minutes, the coercive force reduction rate δH expressed by the following formula (2) was c 2. The highly heat-resistant Sm-Fe-N magnetic powder according to claim 1, wherein the content of the magnetic flux is 60% or less. δH c =100×(H c0 -H c1 ) / H c0 …(2) Here, H c0 is the coercive force (kA / m) of the powder before the heating test, H c1 is the coercive force (kA / m) of the powder after the heating test.

7. A method for producing a highly heat-resistant Sm-Fe-N magnetic powder, comprising: a film-forming process for forming a coating layer of an Al-Ae alloy on the surfaces of particles constituting the Sm-Fe-N magnetic powder, which is a film-forming material, by a vapor phase growth method, where Ae is an alkaline earth metal element.

8. 8. The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to claim 7, wherein the vapor phase growth method is a sputtering method, and in the film-forming step, a coating layer of an Al-Ae alloy is formed on the surface of particles constituting the Sm-Fe-N magnetic powder by a sputtering method while stirring and flowing the Sm-Fe-N magnetic powder, which is the material to be film-formed, in a sputtering film-forming device.

9. The method for producing a high heat-resistant Sm-Fe-N magnetic powder according to claim 7, wherein the Sm-Fe-N magnetic powder, which is a film-forming material, has a composition in which the Sm / Fe molar ratio is 0.09 or more and 0.25 or less, and the N / Fe molar ratio is 0.06 or more and 0.30 or less.

10. The Sm-Fe-N magnetic powder, which is the material to be deposited, has a cumulative 50% particle diameter D 50 8. The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to claim 7, wherein, in the film-forming step, Al and an alkaline earth metal element Ae are deposited so that a coverage index R expressed by the following formula (1) is 0.10 μm or more and 2.00 μm or less. Coverage index R = [(Al + Ae) / Fe] × D 50 …(1) Here, the value of the (Al+Ae) / Fe molar ratio in the powder having an Al-Ae alloy coating layer is substituted for [(Al+Ae) / Fe] in the formula (1), and D 50 The cumulative 50% particle diameter D 50 The value of (μm) is substituted.

11. 11. The method for producing a highly heat-resistant Sm-Fe-N magnetic powder according to claim 10, wherein in the film-forming step, Al and an alkaline earth metal element Ae are deposited so that the coverage index R is 0.10 μm or more and 1.00 μm or less.

12. The Sm-Fe-N magnetic powder, which is a film-forming material, a heat treatment process for coarsening the crystal grains of the powder particles by heating the powder of the Sm-Fe alloy having a Sm / Fe molar ratio of 0.09 or more and 0.25 or less, which is formed in the solidification process by the gas atomization method, to a temperature of 900° C. or more and 1200° C. or less; a crushing step of crushing the powder of the Sm—Fe alloy, the crystal grains of which have become coarse by the heat treatment step, to thereby reduce the particles of the powder by fracture, including intragranular fracture; a nitriding step of introducing nitrogen into the particles of the Sm—Fe alloy powder refined by the pulverization step by heating and holding the powder at a temperature range of 500° C. or less in a nitrogen compound or nitrogen-containing non-oxidizing gas atmosphere; The method for producing the highly heat-resistant Sm-Fe-N magnetic powder according to claim 7, wherein the highly heat-resistant Sm-Fe-N magnetic powder is obtained by a production method having the steps of:

13. a densification treatment step of heating the Sm—Fe—N magnetic powder obtained in the film-forming step in a non-oxidizing atmosphere to a temperature T (° C.) that satisfies the following formula (4); The method for producing high heat-resistant Sm-Fe-N magnetic powder according to claim 7, further comprising: 450≦T(℃)≦550 ... (4)

14. In the film forming process, the melting start temperature T M forming an Al-Ae based alloy coating layer having a composition in which the temperature is 600° C. or less, a densification treatment step of heating the Sm—Fe—N magnetic powder obtained in the film-forming step in a non-oxidizing atmosphere to a temperature T (° C.) that satisfies the following formula (3); The method for producing high heat-resistant Sm-Fe-N magnetic powder according to claim 7, further comprising: T M (℃)-100≦T(℃)≦550 …(3)

Citation Information

Patent Citations

  • Rare earth-iron-nitrogen magnetic powder, compound for bond magnets, bond magnet and method for producing rare earth-iron-nitrogen magnetic powder

    JP2022177699A